Initial Evidence for the Reliability and Validity of the Student Risk Screening Scale for Internalizing and Externalizing Behaviors at the Middle School Level. (December 2013) - Lane, Kathleen Lynne; Oakes, Wendy Peia; Carter, Erik W.; Lambert, Warren E.; Jenkins, Abbie B.
We reported findings of an exploratory validation study of a revised universal screening instrument: the Student Risk Screening Scale–Internalizing and Externalizing (SRSS-IE) for use with middle school students. Tested initially for use with elementary-age students, the SRSS-IE was adapted to include seven additional items reflecting characteristics of internalizing behaviors. The initial seven items developed by Drummond (1994) were retained, yielding a modified instrument containing 14 items (SRSS-IE14) rated by teachers on the original 4-point, Likert-type scale. First, we examined reliability of SRSS-IE14 scores by analyzing item-level data, internal consistency estimates, and factor structure with a sample of 937 middle school students. Results of a data analytic plan grounded in Classical Test Theory supported retention of five of the new seven items, producing the SRSS-IE12. Second, we established convergent validity of the SRSS-IE12 with the Strengths and Difficulties Questionnaire (Goodman, 1997), a validated screening tool. We offered recommendations for addressing the limitations of this study in future research.